Meaningful Data Sharing: Developing the Illinois Data Bank Metadata Framework. Issue 2 (3rd April 2018) - Stein, Ayla; Dunham, Elise
Abstract: In Summer 2016, the Illinois Data Bank, the new data repository at the University of Illinois at Urbana-Champaign, was launched. This paper will cover the development of the repository's metadata schema, including the team's decisions in balancing external and internal stakeholder requirements, finding solutions to challenges both foreseen and not, as well as future plans.